HOTS Analysis and Learning Independence: Class 10 Biology Learning Using Multiple Representation Models - Sari, Eka Puspita; Haka, Nukhbatul Bidayati; Supriyadi, Supriyadi (IJIS Edu : Indonesian Journal of Integrated Science Education, 2022)
The application of learning models that are not in accordance with the abilities and intellectual background of students makes learning activities not optimal so as to make Higher Order Thinking Skills and learning independence of students low. The effort made is to apply a model that presents a variety of representations so that students can be given the opportunity to receive information according to their abilities, namely the Multiple Representation model. This study aims to determine the effect of the Multiple Representation model on HOTS and the learning independence of grade 10 students in Biology at SMA Muhammadiyah 2 Bandar Lampung. Data collection techniques include essay questions, questionnaires, and documentation. The results showed that the students' HOTS Posttest scores were in the good category with an average N-gain for the experimental class of 0.63 and an average N-gain for the control class of 0.35. The same is true for the posttest scores of students' learning independence with an average N-gain for the experimental class of 0.54 and an average N-gain for the control class of 0.15. The results of data analysis show that the data is normal and homogeneous. The results of hypothesis calculations with the Manova test show that the Sig value is 0.000 <0.05, then H0 is rejected and H1 is accepted. It can be concluded that there is an effect of the Multiple Representation model on HOTS and Learning Independence of 10th grade students in Biology at SMA Muhammadiyah 2 Bandar Lampung.